Pendampingan dan Pelatihan dalam Pembuatan Eco-Enzyme dengan Memanfaatkan Limbah Organik di Kecamatan Hatonduhan - Situmorang, Masni Veronika; Silalahi, Mastiur Verawaty; Siagian, Gunaria (Universitas Pahlawan Tuanku Tambusai, 2024)
This mentoring and training activity aims to reduce organic waste produced by households and convert it into environmentally friendly products. Implementation can be done through making eco enzymes that can be applied in households. Eco enzyme is a product made from the fermentation reaction of organic waste with brown sugar. Eco enzymes can be made by mixing organic waste, brown sugar/molasses, and water with a mass ratio of 3:1:10. This service activity consists of preliminary, implementation and evaluation stages. In the preliminary stage the team prepared the eco enzyme material. Then, at the implementation stage, assistance activities were carried out in making eco enzymes. Next, at the evaluation stage, a questionnaire is filled out regarding the implementation of service. From the results of the questionnaire it was found that 85.71% were very interested in eco enzymes, as many as 91.43% of residents would make eco enzymes at home by utilizing organic waste from households, as many as 74.29% of residents wanted to develop a business from eco enzyme products, As many as 91.43% of residents wanted to use eco enzyme products in household activities and as many as 85.71% of residents expressed satisfaction with the socialization and assistance activities for making eco enzymes that had been carried out. Through this activity, it is hoped that residents will be more creative and innovative in processing organic waste.